Kemampuan Mahasiswa PPL Jurusan Pendidikan Guru Madrasah Ibtidaiyah dalam Pengelolaan Kelas - Salmah, Syarifah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2014)
This study was aimed to know the students’ ability in managing classroom in the internship program of teaching. As future teacher, the students are directed to master on the skills of teaching. One of the skills is pedagogical skill to manage the classroom. This study used a descriptive design. The data was collected by using observation. The population of the study was the internship program students of semester VI of Madrasah Ibtidaiyah study program. The sampling used random sampling with 11 students sample. The result of finding shows that the highest score was 75 and the lowest score was 50. The students who were in the category of “Very Good” or in the range of 71-85, was 18.2% (2 of 11 students), in the category of “Good” or in the range of 56-85 was 36.4% (4 of 11 students), in the category of “Good Enough” or in the range of 41-55 was 45.4% (5 of 1 students), and no students were in the category of “Poor” or in the range of 26-40.